The Musical Encart of the Royal Printers Le Roy & Ballard in the 1583 Hours of Jamet Mettayer Held in the Musée de l’Amérique francophone in Quebec City - Bazinet, Geneviève B. (Renaissance and Reformation / Renaissance et Réforme, 2016)
The Heures de Nostre Dame, a l’usage de Rome: selon la Reformation de Nostre S. Pere pape Pie VI pour la Congregation roiale des penitens de l’Annonciation de Nostre Dame, printed at the request of King Henri III by Royal Printer Jamet Mettayer (Paris, 1583) and held at the Musée de l’Amérique francophone in Quebec City, is a rare example of a Book of Hours that contains music. The musical encart printed by the Royal Printers of Music Le Roy & Ballard (Paris, 1583) follows the texts of the Hours and totals thirty-six pages. This article focuses on the music in the encart and its relationship to the rest of the book, and on references to music in the statutes of the Congrégation. The musical encart is an essential part of this Book of Hours as it provides music for the Hours of the Virgin and the other offices celebrated by the Congrégation, as well as insight into their musical performance practices.